Mean-variance cointegration and the expectations hypothesis - Till Strohsal; Enzo Weber (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2011)
The present paper sheds further light on a well-known (alleged) violation of the expectations hypothesis of the term structure (EHT) - the frequent finding of unit roots in interest rate spreads. We show that the EHT implies (i) that the nonstationarity stems from the holding premium, which is hence (ii) cointegrated with the spread. In a stochastic discount factor framework we model the premium as being driven by the integrated variance of excess returns. Introducing the concept of mean-variance cointegration we actually find cointegration relations between spreads and premia in US data.
Keywords: E43; C32; 330; expectations hypothesis; holding premium; persistence; cointegration; GARCH; Zinsstrukturtheorie; Risikoprämie; Kointegration; ARCH-Modell; Schätzung; USA